2021
DOI: 10.3390/cancers13081947
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Run Next-Generation Sequencing (NGS) Assay for the Simultaneous Detection of Both Gene Mutations and Large Chromosomal Abnormalities in Patients with Myelodysplastic Syndromes (MDS) and Related Myeloid Neoplasms

Abstract: Myelodysplastic syndromes (MDS) and myelodysplastic/myeloproliferative neoplasms are clonal disorders that share most of their cytogenetic and molecular alterations. Despite the increased knowledge of the prognostic importance of genetics in these malignancies, next-generation sequencing (NGS) has not been incorporated into clinical practice in a validated manner, and the conventional karyotype remains mandatory in the evaluation of suspected cases. However, non-informative cytogenetics might lead to an inadeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(52 reference statements)
2
6
0
Order By: Relevance
“…This is the first study to assess the detection of cytogenetic alterations in cfDNA by NGS in a cohort of patients with MDS. Other studies have used NGS to detect these chromosomal alterations in PB or BM samples, 28 and only 1 study used cfDNA to identify the loss of chromosome 9 in cfDNA in a patient with MDS. 11 …”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to assess the detection of cytogenetic alterations in cfDNA by NGS in a cohort of patients with MDS. Other studies have used NGS to detect these chromosomal alterations in PB or BM samples, 28 and only 1 study used cfDNA to identify the loss of chromosome 9 in cfDNA in a patient with MDS. 11 …”
Section: Discussionmentioning
confidence: 99%
“…According to the data reported by Papaemmanuil et al, cytogenetic anomalies were found in about 40–50% of MDS patients [ 16 ]; the most common chromosomal abnormalities are the loss of chromosome 7, deletions of the long arm of chromosomes 5 and 7, and gains of some chromosomes, such as chromosomes 8, 19, and 21 [ 18 , 19 , 20 ].…”
Section: Cytogenetic Of Mds Progressionmentioning
confidence: 99%
“…Identifying genetic mutations and determining how these gene mutations work together to produce MDS phenotypes can help researchers in the eld better understand the pathogenesis of MDS and how MDS translates into acute leukemia. Over the decades, advances in technology have made it possible to identify new genetic mutations in MDS, including SNP array analysis and next-generation sequencing (NGS) identi ng genes that are repeatedly mutated in MDS [13], and the application of whole genome sequencing and exome sequencing can identify more prognostically relevant genetic mutations [14], which not only facilitates targeted drug research against genetic mutations, but also promotes con dence in using genomic, transcriptome, and clinical data to group MDS more granularly for prognostic grouping [15]. In short, gene mutation is a necessary condition for the change of disease phenotype, which provides great possibilities for revealing the internal law of MDS disease.…”
Section: Cluster2 and Cluster6mentioning
confidence: 99%